Energy Efficiency Analysis of a Hydraulic Power Unit (HPU) System on a Winch during Tensile Load Testing - Faizin Faiz; Komarudin Komarudin (Greenation International Journal of Engineering Science, 2025)
This study aims to analyze the energy efficiency of a Hydraulic Power Unit (HPU) system in driving a winch during tensile load testing. Experiments were conducted on a hydraulic winch with a maximum capacity of 10 tons by applying tensile loads gradually from 2 to 10 tons. The measured parameters include hydraulic pressure, flow rate, pulling force, and rope winding speed. Hydraulic input power and mechanical output power were calculated to evaluate system efficiency. The results indicate that the HPU system is capable of operating the winch stably under all tested load conditions. System efficiency tends to increase from low to medium load levels and then becomes relatively constant or slightly decreases at higher loads due to increasing energy losses caused by mechanical friction, internal leakage, and pressure drops in the hydraulic system. These findings suggest that proper selection of operating parameters and regular maintenance of hydraulic components are essential to improve the overall energy efficiency and reliability of HPU-driven winch systems.